PROTOTYPE DESIGN OF DIFFERENTIATION STRATEGY APPLICATION: (Case Study on Restaurants at Medan City) - Kartini Harahap (Jurnal Ekonomi, 2022)
The study aims to design application concepts and prototypes of differentiation strategies in achieving competitive advantage in restaurants using a design thinking model (a case study on a restaurant at Medan City), related to the problem of restaurants that must be able to deal with the COVID-19 pandemic situation amid of a highly competitive environment. The study used a descriptive qualitative approach and used purposive random sampling for sampling. The type of data used is primary and secondary data with data collection through interviews, observation and documentation. Data analysis uses value chain analysis, and design thinking models. The results showed that the conceptual design in building the application of a differentiation strategy to achieve competitive advantage in restaurants consisted of four data pillars, namely (i) identification, (ii) analysis of potential sources of differentiation, (iii) creating differentiation, and (iv) restaurant value chains. The prototype built on the application of a restaurant's differentiation strategy consists of five differentiations, namely: (i) product differentiation, (ii) service differentiation, (iii) place differentiation, (iv) personnel differentiation, and (v) channel differentiation. This research is expected to be able to build an application of competitive strategy through an effective differentiation strategy, making it easier for restaurant business people to develop and define differentiation strategies in achieving competitive advantage and provide opportunities for restaurant businesses to always innovate in strategies that are adaptive to any changes in the dynamic and complex environment.